Perancangan Berorientasi Objek pada Pembangunan Aplikasi Pemasaran dan Pengolahan Ikan - Gusriva, Revi; Sentosa, Rio Bayu; Randa, Dimas Dwi (LPPM STIKOM Tunas Bangsa, 2024)
The development of information technology has made significant contributions to various fields, including the fishing industry. The Marine and Fisheries Office of West Sumatra Province, particularly in the Field of Enhancing Marine and Fisheries Competitiveness, requires an effective and efficient fish marketing and processing application to improve the competitiveness and productivity of fishermen in West Sumatra. This study aims to design a fish marketing and processing application using an object-oriented approach. This approach is chosen for its ability to model systems more naturally and intuitively, as well as facilitate system maintenance and future development. In the design of this application, the Unified Modeling Language (UML) method is used to visualize the system design. UML provides a set of diagrams that can comprehensively depict the structure and behavior of the system. Some of the diagrams used include use case diagrams, class diagrams, and activity diagrams. This application is built based on the information needs regarding fish prices, ornamental fish, restaurants, fish exports, and various fish products by the community, business actors, and the government, monitoring all fishery products online, and facilitating field officers in data entry.